EVIDENCE BASED CASE REPORT (EBCR) : PEMBERIAN MADU DAPAT MENURUNKAN FREKUENSI DIARE PADA BALITA DI PUSKESMAS PADASUKA (Politeknik Kesehatan Kemenkes Bandung, 2022)
Background: The prevalence of diarrhea is still high at 40% and 2nd ranks after pneumonia. The prevalence of diarrhea is still above the national target of 10%. Several attempts to treat diarrhea in toddlers have been carried out. There are non-pharmacological efforts that can help accelerate the healing of diarrhea, namely by giving honey. Honey is a type of drink that contains probiotic agents that are antibacterial, which contain inhibine, glycosides, and polyvenols. This content can inhibit the metabolic process of microorganisms such as eschericia coli as one of the diarrhea. Purpose: The purpose of this evidence based case report was to determine efforts to reduce the frequency of diarrhea by giving honey to people with diarrhea. Method:This study uses a literature review method. Result: The results of the analysis of the literature review from the evidence based cased report study showed that honey reduced the duration of diarrhea and accelerated recovery time. The intervention of giving honey to toddlers who have diarrhea has been resolved. Conclusion: It can be concluded that giving honey can be an alternative in helping to treat and to recover from diarrhea